Study of highly sensitivity metal wires assisted photonic crystal fiber based refractive index sensor - Ramani U.; Kumar H.; Singh B.K.; Pandey P.C. (My University, 2025)
In this paper, a photonic crystal fiber (PCF) sensor based on surface plasmon resonance is proposed for refractive index (RI) sensing with improved sensitivity and resolution. In this design, solid core PCF with three layers of holes is used. Instead of a coating metal layer, we have used two metal wires at both sides of the outside layer of fiber to originate surface plasmon resonance for detection of RI of analyte effectively. Design and analyses have been performed by a Full vectorial finite element method (FV-FEM). Metals Cu, Au, and Ag have been used as plasmonic materials that exhibit higher wavelength sensitivity 7300 nm/RIU, 6200 nm/RIU, and 6100 nm/RIU, respectively. For Cu metal, we observe maximum amplitude sensitivity 597 RIU−1 with higher resolution 1.36 × 10–5 RIU for refractive index of range 1.31–1.36. However, the average sensitivity for Cu, Au, and Ag are 4320 nm/RIU, 4275 nm/RIU, and 3950 nm/RIU, respectively. The effect of air holes along with metal wires for sensitivity is also investigated. In results, copper has provided better sensitivity as well as resolution for a long-range analyte for this proposed RI sensor. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.